Registration of aphid‐resistant 'California Blackeye 77' cowpea. Issue 1 (3rd October 2021) - Huynh, Bao‐Lam; Duong, Tra; Clark, Nicholas E.; Long, Rachael; Light, Sarah E.; Dahlquist‐Willard, Ruth M.; Ehlers, Jeffrey D.; Close, Timothy J.; Roberts, Philip A.
Abstract: 'California Blackeye 77' (CB77) (Reg. no. CV‐344, PI 698656) is a blackeye‐type cowpea [ Vigna unguiculata (L.) Walp] cultivar developed by the University of California, Riverside. CB77 is distinguished from the industry standard cultivars, 'California Blackeye 46' (CB46) and 'California Blackeye 5' (CB5), by its ability to resist infestation caused by cowpea aphid ( Aphis craccivora Koch), a destructive sap‐sucking insect pest prevalent in the Central Valley of California and warm‐to‐hot regions worldwide. CB77 was developed by introgression of two known quantitative trait loci for aphid resistance from the African cowpea breeding line IT97K‐556‐6 into CB46 through marker‐assisted backcrossing. Genotyping with 51, 128 single nucleotide polymorphism markers reveals that CB77 is near‐isogenic to CB46 and carries two resistance haplotypes (∼4 Mb in total) from IT97K‐556‐6. On‐station and on‐farm trials with aphid infestations confirmed the inherent resistance in CB77 (aphids covered 0–10% of plant surface area without causing any crown damage, whereas check CB46 had aphids covering 60–70% of plant surface area and causing severe crown damage). Under protected conditions, CB77 showed grain yield, seed quality, and other agronomic characteristics equivalent to CB46 and better yield than CB5. CB77 could therefore be substituted for CB46 and CB5 in production regions where aphids are present. The near‐isogenic pair CB77 and CB46 are also useful materials for resistance gene discovery. Core Ideas: CB77 is statistically higher than the current commonly grown cultivar CB46 for aphid resistance. CB77 has seed yield and quality equivalent to or better than CB46 based on multi‐year trials. Marker data for CB77 and founder parents could be useful in fine mapping of resistance genes.